An exploration of the validity and reliability of "Managerial Reading Assessment", a cognitive ability test : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - O'Hare, Mary Alice (Massey University, 1999)
Cognitive ability tests are generally considered in the empirical literature to be one of the most valid predictors for selecting managerial level staff. However, very few of these tests have been specifically designed and developed for managers. Managerial Reading Assessment (MRA) is an original cognitive ability test which has been created for this purpose. Because critical thinking skills, particularly the ability to draw inferences, are regarded as being crucial to the successful performance of a manager's job, this test specifically targets this skill. The present study investigated the validity and reliability of Managerial Reading Assessment (MRA) to assess its potential as a selection test for managers. A total of 97 voluntary participants, the majority of whom were drawn from junior to senior levels of management, were recruited from their place of work to take part in this research. Respondents were asked to complete the test and return it by mail. To evaluate the validity of the MRA, two criterion measures (salary and highest educational level achieved) were adopted. When education was utilised as the criterion, a validity coefficient of rho=0.39 was obtained, significant at the 0.01 level. The size of this correlation is comparable to those obtained for other cognitive ability tests. The internal consistency of the test was computed using the alpha coefficient. The results indicate that this test is also reliable. More study would need to be conducted to further assess the psychometric properties of this test.
Keywords: Industrial Psychology; Cognitive psychology; Oranisational behavior; Management; Psychological aspects; Testing